Renal impairment after ileostomy formation: a frequent event with long‐term consequences. (17th October 2019) - Fielding, A.; Woods, R.; Moosvi, S. R.; Wharton, R. Q.; Speakman, C. T. M.; Kapur, S.; Shaikh, I.; Hernon, J. M.; Lines, S. W.; Stearns, A. T.
Abstract: Aim: High stoma output and dehydration is common following ileostomy formation. However, the impact of this on renal function, both in the short term and after ileostomy reversal, remains poorly defined. We aimed to assess the independent impact on kidney function of an ileostomy after rectal cancer surgery and subsequent reversibility after ileostomy closure. Methods: This retrospective single‐site cohort study identified patients undergoing rectal cancer resection from 2003 to 2017, with or without a diverting ileostomy. Renal function was calculated preoperatively, before ileostomy closure, and 6 months after ileostomy reversal (or matched times for patients without ileostomy). Demographics, oncological treatments and nephrotoxic drug prescriptions were assessed. Outcome measures were deterioration from baseline renal function and development of moderate/severe chronic kidney disease (CKD ≥ 3). Multivariate analysis was performed to assess independent risk factors for postoperative renal impairment. Results: Five hundred and eighty‐three of 1213 patients had an ileostomy. Postoperative renal impairment occurred more frequently in ileostomates (9.5% absolute increase in rate of CKD ≥ 3; P  < 0.0001) vs no change in patients without an ileostomy ( P  = 0.757). Multivariate analysis identified ileostomy formation, age, anastomotic leak and renin–angiotensin system inhibitors as independently associated with postoperative renal decline. Despite stoma closure, ileostomates remained at increased risk of progression to new or worse CKD [74/438 (16.9%)] compared to patients without an ileostomy [36/437 (8.2%), P  = 0.0001, OR 2.264 (1.49–3.46)]. Conclusions: Ileostomy formation is independently associated with kidney injury, with an increased risk persisting after stoma closure. Strategies to protect against kidney injury may be important in higher risk patients (elderly, receiving renin–angiotensin system antihypertensives, or following anastomotic leakage).